GOALS AND MOTIVES IN THE CHOICE OF A UNIVERSITY COURSE: A COMPARATIVE STUDY BETWEEN LAW , BIOLOGY AND PSYCHOLOGY STUDENTS - Gámez, Elena; Marrero, Hipólito (Anales de Psicología / Annals of Psychology, 2003)
The main goal of this paper was to know which type of goals and motives students have when they decide to start university courses. We designed a questionnaire with items that included personal goals, social and relationship motives and learned goals. The questionnaire was completed by a sample of 513 students of psychology, law and biology, 170 men and 343 women. With the matrix of data we performed factorial analyses and the results were explained for the whole sample and for each type of study. The results show differences and similarities in the pattern of goals and motives as a function of the course and thegender of the students.